Recently photoassimilated carbon and fungus‐delivered nitrogen are spatially correlated in the ectomycorrhizal tissue of Fagus sylvatica. Issue 6 (6th August 2021) - Mayerhofer, Werner; Schintlmeister, Arno; Dietrich, Marlies; Gorka, Stefan; Wiesenbauer, Julia; Martin, Victoria; Gabriel, Raphael; Reipert, Siegfried; Weidinger, Marieluise; Clode, Peta; Wagner, Michael; Woebken, Dagmar; et al.
Summary: Ectomycorrhizal plants trade plant‐assimilated carbon for soil nutrients with their fungal partners. The underlying mechanisms, however, are not fully understood. Here we investigate the exchange of carbon for nitrogen in the ectomycorrhizal symbiosis of Fagus sylvatica across different spatial scales from the root system to the cellular level. We provided 15 N‐labelled nitrogen to mycorrhizal hyphae associated with one half of the root system of young beech trees, while exposing plants to a 13 CO2 atmosphere. We analysed the short‐term distribution of 13 C and 15 N in the root system with isotope‐ratio mass spectrometry, and at the cellular scale within a mycorrhizal root tip with nanoscale secondary ion mass spectrometry (NanoSIMS). At the root system scale, plants did not allocate more 13 C to root parts that received more 15 N. Nanoscale secondary ion mass spectrometry imaging, however, revealed a highly heterogenous, and spatially significantly correlated distribution of 13 C and 15 N at the cellular scale. Our results indicate that, on a coarse scale, plants do not allocate a larger proportion of photoassimilated C to root parts associated with N‐delivering ectomycorrhizal fungi. Within the ectomycorrhizal tissue, however, recently plant‐assimilated C and fungus‐delivered N were spatially strongly coupled. Here, NanoSIMS visualisation provides an initial insight into the regulation of ectomycorrhizal C and N exchange at the microscale.